Novel Application of Hydrotropic Solubilization in theSpectrophotometric Analysis of Cephalexin in Solid Dosage Form - Maheshwari, R.K.; Pandey, S.P.; Lovlekar, Apeksha; Chavda, V.; Ajmera, Arpita; Gupta, H.M. (Asian Journal of Chemistry, 2010)
In the present investigation, cephalexin has been selected as a poorly water-soluble model drug. There was more than 6-fold enhancement in aqueous solubility of cephalexin by 8.0 M urea solution (as compared to aqueous solubility). This hydrotropic agent was employed to solubilize the drug from the fine powder of tablet formulations. The selected λmax for spectrophotometric estimation was 262 nm. The hydrotropic agent and the additives used in the manufacture of tablets did not interfere in the analysis. Proposed method is new, rapid, simple, accurate and reproducible. Statistical data prove the accuracy, reproducibility and the precision of the proposed method.